Inhibitory effect of clonidine upon adenylate cyclase activity, cyclic AMP production, and insulin release in rat pancreatic islets. Issue 6 (June 1984) - Garcia-Morales, P.; Dufrane, S. P.; Sener, A.; Valverde, I.; Malaisse, W. J.
Abstract : Conflicting opinions were recently expressed concerning the possible effect of α2 -adrenergic agonists upon cyclic AMP production in pancreatic islets. In the present: study, clonidine inhibited glucose-induced insulin release from rat pancreatic islets, this inhibitory effect being abolished by idazoxan. Clonidine did not suppress the capacity of forskolin to augment glucose-induced insulin release. In a particulate subcellular fraction derived from the islets, adenylate cyclase was activated by calmodulin (in the presence of Ca 2+ ), NaF, GTP, L-arginine, and forskolin, and slightly inhibited by clonidine. The inhibitory action of clonidine upon basal adenylate cyclase activity was more pronounced in islet crude homogenates. The inhibitory effect of clonidine was antagonized by forskolin whether in the particulate fraction or crude homogenate. At variance with the modest effects of glucagon, D-glucose, L-arginine, or a tumor-promoting phorbol ester upon cyclic AMP production by intact islets, forskolin caused a six-fold increase in cyclic AMP production. Clonidine inhibited cyclic AMP production by intact islets, whether in the absence or presence of forskolin. It is proposed that the inhibitory action of clonidine upon insulin release is attributable, in part at least, to inhibition of adenylate cyclase.